Simultaneous Spectrophotometric Determination of Copper(II) and Nickel(II) Using Dimethylglyoxime as a Reagent - Muralikrishna, U.; Sivaramakrishna, Akella (Asian Journal of Chemistry, 2010)
Conditions have been developed for the simultaneous determination of copper(II) and nickel(II) in mixtures using ammoniacal dimethylglyoxime solution as a reagent. The Beer's law ranges for copper(II) and nickel(II) are 5.1-91.6 and 0.2-2.5 μg/mL at 590 nm and 440 nm respectively. The molar absorptivity is 2.42 x 102 1. mol-1 cm-1 for copper(II) at 590 nm and 1.44 x 104 1.mol-1 cm-1 for nickel(II) at 440 nm. Effect of diverse ions has been studied. The method is applied successfully in some alloys as well as in synthetic mixtures.